Salmonella osteomyelitis complicating aseptic osteonecrosis: Don't forget about the antiphospholipid syndrome. Issue 4 (11th March 2021) - Daoud, Fatma; Rachdi, Imène; Frikha, Olfa; Ben Salah, Mohamed; Charaa, Soumaya; Zoubeidi, Hana; Somai, Mehdi; Hadhri, Khaled; Kooli, Mondher; Chammakhi, Chiraz; Boussema, Fatma
Abstract: Osteonecrosis in antiphospholipid syndrome is a diagnostic challenge for clinicians. Early diagnosis and intervention are important for better prognosis. Abstract : Osteonecrosis in antiphospholipid syndrome is a diagnostic challenge for clinicians. Early diagnosis and intervention are important for better prognosis.